Declining water yield from forested mountain watersheds in response to climate change and forest mesophication. (26th May 2016) - Caldwell, Peter V.; Miniat, Chelcy F.; Elliott, Katherine J.; Swank, Wayne T.; Brantley, Steven T.; Laseter, Stephanie H.
Abstract: Climate change and forest disturbances are threatening the ability of forested mountain watersheds to provide the clean, reliable, and abundant fresh water necessary to support aquatic ecosystems and a growing human population. Here, we used 76 years of water yield, climate, and field plot vegetation measurements in six unmanaged, reference watersheds in the southern Appalachian Mountains of North Carolina, USA to determine whether water yield has changed over time, and to examine and attribute the causal mechanisms of change. We found that annual water yield increased in some watersheds from 1938 to the mid‐1970s by as much as 55%, but this was followed by decreases up to 22% by 2013. Changes in forest evapotranspiration were consistent with, but opposite in direction to the changes in water yield, with decreases in evapotranspiration up to 31% by the mid‐1970s followed by increases up to 29% until 2013. Vegetation survey data showed commensurate reductions in forest basal area until the mid‐1970s and increases since that time accompanied by a shift in dominance from xerophytic oak and hickory species to several mesophytic species (i.e., mesophication) that use relatively more water. These changes in forest structure and species composition may have decreased water yield by as much as 18% in a given year since the mid‐1970s after accounting for climate. Our results suggest that changes in climate and forest structure and species composition in unmanaged forests brought about by disturbance and natural community dynamics over time can result in large changes in water supply.